List of Medieval Religious Houses on Islands: Norway - Wehrle, Franziska (The journal of medieval monastic studies, 2021)
The paper offers a survey of monastic island communities in Medieval Norway, including brief historical descriptions of their foundation, patrons, dissolution, sources, remaining building structures, and - if available - information regarding economic activities and wealth. Far from having been isolated places of retreat, Norwegian island monasteries were situated on ideal landing places, nodal points close to important economic centres of the time. The island locations might be interpreted as advantages for the nuns and monks, in terms of facilitating strategic defence, economic stability, and regular incomes from fishing grounds or customs revenues. No preference for island locations amongst the different orders can be recognized. Nuns and monks, Benedictines, Cistercians, the canons and also the Franciscans are amongst the monastic island dwellers. Halsnøy island seems to have housed for some time the most northern Hospital of the Order of the Holy Spirit (Rome).